BJ Habibie's Transformational Leadership in Indonesia's Political Transition Post-New Order - Rahmi Septia Frisye; Hasnah Faizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the transformational leadership of President BJ Habibie during Indonesia's post–New Order political transition using a qualitative descriptive approach with a case study design. The research focuses on Habibie's leadership style, reform policies, and strategic role in building the foundation of Indonesian democracy. Data were obtained through a literature review of books, journal articles, and policy documents, then analyzed using content analysis through data reduction, data display, and conclusion drawing. The findings reveal that Habibie demonstrated transformational leadership characterized by visionary reform, innovative policymaking, and high political morality. He initiated major reforms such as the abolition of the military's dual function, press liberalization, the first democratic election in 1999, and regional autonomy. These policies served as milestones in Indonesia's transition toward a more open and participatory political system. The study concludes that Habibie's transformational leadership played a pivotal role in shaping Indonesia's democratization process and stands as a model of adaptive political leadership in developing countries.